Engineering of educational programs through the application of intelligent technologies - Mikhail S. Gasparian; Sergey A. Lebedev; Yury F. Telnov (Открытое образование (Москва), 2017)
One of the key tasks of the present stage of the education system development in Russia is to improve the practical orientation of specialists’ training for the modern labor market. On the agenda, there are the issues of modernization of educational programs in the direction of a closer relationship between education and professional standards, which is the main purpose of this study.Rapidly changing business needs, especially in the field of the booming ITindustry indicate the need for continuous improvement of mechanisms for the acquisition of new knowledge, abilities and skills of students, which in turn requires the development of special tools for the development of educational technologies. The article discusses the issues of flexible engineering education programs of higher education in accordance with the needs of the labour market, presented in professional standards. The methods of semantic modeling of informational and educational space, allowing to systematize the knowledge of the professional area in the form of conceptual models of ontologies and repositories of learning objects are offered as the methods of engineering.As the result of the correlation analysis of the categories of existing educational and professional standards, the mechanism to overcome the contradictions between the language of professional competences of educational standards and requirements of the labour functions of the professional standards is proposed. The paper describes the characteristics of the knowledge and skills of educational programs in the categories: scope, sphere and types of tasks of professional activities.The professional competences are differentiated due to profiles of training and types of professional tasks.The proposed universal algorithm for the development of educational programs of profile training on the base of the analysis of generalized labour functions and labour functions of professional standards can be useful to specialists, involved in designing of the basic professional educational programs on a wide range of directions and profiles of training